(untitled) (Margalla Papers, 2024)
The landmark peace deal between Iran and Saudi Arabia brokered by China has ended years of hostility between the two regional arch-rivals. The peace agreement is expected to ease the regional tension and bring peace and stability. The warming up of relations may also lead to the end of proxy wars in Yemen, Syria and Iraq. China’s emergence as a non-hegemonic and reliable extra-regional actor/guarantor would stabilise the regional security environment. This development directly impacts Pakistan as it has good relations with Iran, Saudi Arabia, and China. The peace agreement holds great prospects for Pakistan through investment, trade, joint production, corridor connectivity and joint consortium. However, while the prospects are bright, there are many challenges to harness these opportunities fully. Bibliography Entry Hussain, Nazir. 2024. "Saudi-Iran Peace Agreement: Regional Implications and Prospects for Pakistan." Margalla Papers 28 (1): 16-29.